Bureaucratic Turbulence After the Transfer of Structural to Functional Positions at the Coordinating Ministry for Economic Affairs (Institut Pemerintahan Dalam Negeri, 2022)
This research described the phenomenon of bureaucratic turbulence in the Coordinating Ministry for Economic Affairs after the transfer of structural to functional positions. Furthermore, changes in the organization and individual civil servants were characterized by organizational, position, and performance transformations. The policy of switching functional roles is considered as the most effective method for transforming the lengthy, cumbersome, and slow bureaucratic chain into a new mode of operation based on coordination and collaboration. This research used a qualitative approach that begins with assumptions, perspectives, problem studies, and theoretical used to investigate information from individuals and groups on a social problem. Meanwhile, data collection is carried out by documentation, observation, and literature research to be analyzed and concluded. The results showed that turbulence occurs during the transition period as a process of shifting work culture, behavior, and changes in the mindset of civil servants. The changing needs of the skuel model with a flat circular structure prioritize collaboration and coordination across work groups. Changes in three areas of bureaucratic simplification, such as organizational, position, and performance transformations, resulted in turbulence within the organization. The implementation of functional positions should be reviewed. This is because the implementation requires many apparatus with generalist competency who have greater insight and opportunities to occupy several positions with a wider scope. Generalist competency is needed to link economic affairs across ministries and agencies. Therefore, innovation and problem-solving can be conducted comprehensively through a wider helicopter view.